Determinants within an 18-Amino-Acid U1A Autoregulatory Domain That Uncouple Cooperative RNA Binding, Inhibition of Polyadenylation, and Homodimerization - Guan, Fei (American Society for Microbiology, 2003)
The human U1 snRNP-specific U1A protein autoregulates its own production by binding to and inhibiting the polyadenylation of its own pre-mRNA. Previous work demonstrated that a short sequence of U1A protein is essential for autoregulation and contains three distinct activities, which are (i) cooperative binding of two U1A proteins to a 50-nucleotide region of U1A pre-mRNA called polyadenylation-inhibitory element RNA, (ii) formation of a novel homodimerization surface, and (iii) inhibition of polyadenylation by inhibition of poly(A) polymerase (PAP). In this study, we purified and analyzed 11 substitution mutant proteins, each having one or two residues in this region mutated. In 5 of the 11 mutant proteins, we found that particular amino acids associate with one activity but not another, indicating that they can be uncoupled. Surprisingly, in three mutant proteins, these activities were improved upon, suggesting that U1A autoregulation is selected for suboptimal inhibitory efficiency. The effects of these mutations on autoregulatory activity in vivo were also determined. Only U1A and U170K are known to regulate nuclear polyadenylation by PAP inhibition; thus, these results will aid in determining how widespread this type of regulation is. Our molecular dissection of the consequences of conformational changes within an RNP complex presents a powerful example to those studying more complicated pre-mRNA-regulatory systems.